HUBUNGAN KETERAMPILAN MENYIMAK FILM REMAJA TELEVISI GANTENG-GANTENG SERIGALA DENGAN PEMAHAMAN TEKS DRAMA MAJALAH DINDING SISWA KELAS VIII SMP 2 KRETEK BANTUL YOGYAKARTA - Radhik Martadi; Wijaya Heru Santosa (CARAKA, 2017)
This study aims to describe the level of observing skill of television teen movie Ganteng-Ganteng Serigala, drama text comprehension on eighth-grade students, and prove the existence of a positive and significant relationship between observing television teen movie Ganteng-Ganteng Serigala and comprehension of Majalah Dinding drama text on eighth-grade students of SMP 2 Kretek Bantul. This study uses ex-post facto design. Eighth-grade students of SMP 2 Kretek Bantul are the population of this study. The class population in SMP 2 Kretek Bantul consists of 74 students. An objective test instrument is used to collect the data. It is used to retrieve the data of observing skill of television teen movie and to retrieve the data of drama text comprehension. The instruments of observing skill of television teen movie and drama text comprehension were consulted first to the expert in order to be worthy to use in collecting data and then tested on 29 students. The data from these trials were analyzed by using SPSS 19.0. The data analysis techniques are testing requirements analysis, namely the linearity test, normality test, and test hypotheses. The results showed that: (1) the level of observing skill of television teen movie on eighth grade students of SMP 2 Kretek Bantul belongs to the medium category; (2) the level of understanding drama text of eighth grade students of SMP 2 Kretek Bantul is also in the medium category; (3) there is a positive and significant relationship between observing skill of television teen  movie  Ganteng-Ganteng  Serigala  and  comprehension  of  Majalah Dinding drama text of eighth grade students in SMP 2 Kretek Bantul. This indicates by the r-value of 0.567 in a significance level of 5%. Based on the interpretation of r value according to Arikunto, the value is included in the medium category. Thus, observing skill of television teen movie do not give dominant effect on drama text comprehension. In other words, the habit of observing television teen movie gives a little contribution to  the understanding of the drama text.